Association between benzodiazepine use and exacerbations and mortality in patients with asthma: a matched case-control and survival analysis using the United Kingdom Clinical Practice Research Datalink - Nakafero, Georgina; Sanders, Robert D.; Nguyen-Van-Tam, Jonathan S.; Myles, Puja R. (John Wiley & Sons, 2015)
Purpose: To investigate the association between the GABAergic drugs, benzodiazepines or zopiclone, and the occurrence of asthma exacerbations and subsequent mortality in a cohort of asthma patients. Methods: 105,747 patients without asthma exacerbation and 25,895 patients with exacerbated asthma were included. A nested case-control study probed the association between benzodiazepines or zopiclone and occurrence of asthma exacerbation (primary outcome) using conditional logistic regression. Cox regression was used to determine the association between the drugs and all-cause mortality in patients with recorded asthma exacerbation. Adjusted matched odds ratios (adj mOR), and adjusted hazard ratios (adj HR) with 95% confidence intervals (CI) are presented. Results: Current benzodiazepine use was associated with increased occurrence of asthma exacerbation (adj mOR 1.49; 1.15-1.93; P=0.001) as was current zopiclone use (adj mOR 1.59; 95% CI 1.37-1.85; P<0.001). In patients with an asthma exacerbation, current benzodiazepine use was associated with increased all-cause mortality during a median follow-up of 2 years (adj HR 2.78; 95% CI 1.26-6.12; P=0.011), and the association between zopiclone use and all-cause mortality showed borderline statistical significance (adj HR 1.58; 95% CI 0.98-2.54; P=0.058). Conclusion: Benzodiazepines and zopiclone may increase the likelihood of asthma exacerbation and benzodiazepines may also increase the likelihood of mortality following exacerbation. These data suggest that caution should be exercised when prescribing benzodiazepines to patients with asthma.